New records of injured Cambrian and Ordovician trilobites. (July 2022) - Bicknell, Russell D.C.; Smith, Patrick M.; Howells, Thomas F.; Foster, John R.
Abstract: Records of abnormal fossil arthropods present important insight into how extinct forms responded to traumatic damage and developmental complications. Trilobites, bearing biomineralized dorsal exoskeletons, have arguably the most well-documented record of abnormalities spanning the Cambrian through the end-Permian. As such, new records of malformed, often injured, trilobites are occasionally identified. To further expand the documentation of abnormal specimens, we describe malformed specimens of Lyriaspis sigillum Whitehouse, 1939, Zacanthoides sp. indet., Asaphiscus wheeleri Meek, 1873, Elrathia kingii (Meek, 1870 ), and Ogygiocarella debuchii (Brongniart, 1822 ) from lower Paleozoic deposits. In considering these forms, we propose that they illustrate examples of injuries, and that the majority of these injuries reflect failed predation. We also considered the origin of injuries impacting singular segments, suggesting that these could reflect predation, self-induced damage, or intraspecific interactions during soft-shelled stages. Continued examination of lower Paleozoic trilobite injuries will further the understanding of how trilobites functioned as prey and elucidate how disparate trilobite groups recovered from failed attacks.